Physicochemical Quality of Coffee Soap Based on Variations in Soap Manufacturing Methods and Roasting Type - Wulandari, Sri; Yuwita, Fitri; Anis, Ulfa (Journal of Innovation in Applied Natural Science, 2026)
Background: The demand for natural, environmentally friendly, and sustainable cosmetic products continues to increase along with growing consumer awareness of the negative impacts of synthetic chemicals. Coffee is one of the natural ingredients with potential application in soap formulation, as it contains bioactive compounds beneficial for skin health. Aims: This study aimed to analyze and compare the physicochemical quality of coffee soap based on variations in manufacturing methods (cold process and hot process) and type of coffee roasting (light, medium, and dark). Methods: The research was conducted at the Laboratory of Mathematics and Natural Sciences, University of Bengkulu, and the Laboratory of the Faculty of Agricultural Technology, Gadjah Mada University, using a two-factor Completely Randomized Design (CRD). The quality parameters observed were moisture content, pH, free fatty acids, free alkali and caffeine. Data were analyzed using Two-Way ANOVA. Result: soap making method and the type of coffee roasting had a significant effect on the quality of water content, pH, free fatty acids, and caffeine with a significance value (p<0.05), but had no significant effect on the quality of free alkali (p>0.05) that is 0.136. Conclusion: The combination of the cold process and medium roasting level is recommended as it provides the best balance between the physical and chemical quality of coffee soap. This study contributes to the development of coffee soap as a high-quality and competitive natural cosmetic product